(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main task of the catering company is to prepare meals from food products, organize sales, sell prepared meals, deliver them to customers and provide quality service. In performing the most important task, catering establishments should take the above into account. It is necessary to satisfy the needs of customers with food products, to increase the biological properties, taste and flavor of food, to expand the range. Depending on the type of catering establishment, this task is performed in different ways. In the article it defined very clearly.